Polymer-tethered quenched fluorescent probes for enhanced imaging of tumor associated proteases - Hadzima, Martin; Faucher, Franco; Blažková, Kristýna; Yim, Joshua J; Guerra, Matteo; Chen, Shiyu; Woods, Emily C; Park, Ki Wan; Šácha, Pavel; Šubr, Vladimír; Kostka, Libor; Etrych, Tomáš; et al. (bioRxiv, 2024)
Fluorescence-based contrast agents enable real-time detection of solid tumors and their neovasculature, making them ideal for use in image-guided surgery. Several agents have entered late-stage clinical trials or secured FDA approval, suggesting they are likely to become standard of care in cancer surgeries. One of the key parameters to optimize in contrast agent is molecular size, which dictates much of the pharmacokinetic and pharmacodynamic properties of the agent. Here, we describe the development of a class of protease-activated quenched fluorescent probes in which a N-(2-hydroxypropyl)methacrylamide copolymer is used as the primary scaffold. This copolymer core provides a high degree of probe modularity to generate structures that cannot be achieved with small molecules and peptide probes. We used a previously validated cathepsin substrate and evaluated the effects of length and type of linker as well as positioning of the fluorophore/quencher pair on the polymer core. We found that the polymeric probes could be optimized to achieve increased over-all signal and tumor-to-background ratios compared to the reference small molecule probe. Our results also revealed multiple structure-activity relationship trends that can be used to design and optimize future optical imaging probes. Furthermore, they confirm that a hydrophilic polymer is an ideal scaffold for use in optical imaging contrast probes, allowing a highly modular design that enables efficient optimization to maximize probe accumulation and overall biodistribution properties.
Keywords: iBody; protease; HPMA copolymer; fluorescence; cancer; imaging